Kinetic study of the hydrogenation and hydroisomerization of the n-butenes on a commercial palladium/alumina catalyst - Bressa, Sergio Patricio (2003)
A kinetic investigation of the vapor-phase hydrogenation and hydroisomerization of 1-butene and cis- and trans-2-butene is presented. This investigation is aimed at validating a practical set of rate equations. The experiments were performed at approximately atmospheric pressure using a commercial Pd/Al2O3 catalyst of the eggshell type in an integral fixed-bed isothermal reactor. The outlet composition was measured under 120 sets of operating conditions at six levels of temperature between −8 and 30 °C. The mole fractions of 1-butene and hydrogen in the feed were varied between 0.5 and 3% and between 0.5 and 50%, respectively. Space-time covered the range of (5−55) × 10-3 s. Internal diffusion limitations affected the effective reaction rates and product distribution. Hence, the mass conservation equations inside the catalyst had to be solved to estimate the intrinsic values of the kinetic parameters. Two rival kinetic models of the Langmuir−Hinshelwood−Hougen−Watson type were proposed, one of which could be confidently discriminated as the better of the two models considered. An essential feature of the chosen model is that hydrogen concentration exhibits distinct effects on the hydrogenation and hydroisomerization reactions of n-butenes. The selected model predicts the experimental results with an average deviation of 8.8%. The estimates of the kinetic parameters show inference intervals in the range of ±10−30%.